Evaluation of Sirogonium sticticum, Uronema elongatum, Chroococcus turgidus and Temnogyra reflexa for biodiesel production in Pakistan. Issue 3 (4th May 2017) - Alam, Aftab; Ullah, Saleem; Aftab, Saadia; Alam, Sahib; Khan, Younas; Rahman, Khushnood ur; Zahoor,
ABSTRACT: Algae have emerged as the most promising candidates for commercial-scale biodiesel production. In this study, algae samples were collected from freshwater sources of Khyber Pakhtunkhwa, Pakistan, for their potential for biodiesel production determined by characterizing their oil productivity. The oil content was extracted by Bligh and Dyer, and Soxhlet, methods from the air-dried and oven-dried biomasses, whereas direct and extraction-transesterifications were employed for biodiesel production. Among the 17 species isolated, Chroococcus turgidus, Sirogonium sticticum, Uronema elongatum and Temnogyra reflexa produced the highest oil contents. The Bligh and Dyer method extracted significantly higher oil content than that by the Soxhlet method from the four algae biomasses. Likewise, the biodiesel yield produced by direct transesterification was ∼22% higher than that of extraction-transesterification. Among these algae, C. turgidus gave high biodiesel yield both in the direct and extraction-transesterifications. Notably, there were significantly positive correlations between the oils extracted from either air-dried or oven-dried algae biomasses and biodiesel obtained from the two transesterification methods. It was concluded that local algal species have potential for producing biodiesel. The results suggested prospective approaches to mass cultivation, genetic engineering of local algae, and introduction of high-oil-producing exotic species for high biomass and oil productivity.